School Culture Program: Implementation of School Innovation in the Disruption Era in SDIT Anak Sholeh Mataram Lombok - Emawati (Jurnal Pendidikan Islam, 2019)
This study aims to explore the innovations of Islamic schools in Lombok in the face of the disruption era. SDIT Anak Sholeh Mataram is a representation of a school that made the innovation effort. Data were obtained using the methods of observation, interviews, and documentation. Meanwhile, the theory used to analyze the problem in this study is to adapt the theory of "natural drift." Based on this theory, schools are living systems. The results show that SDIT Anak Sholeh Mataram succeeded in existing and surviving in its interaction and adaptation with its environment. This success was supported by school innovations in the form of a program called "School Culture." This program is a model designed and implemented in order to develop students' personal and social skills. This program emphasizes the practice of religious values ​​in the daily lives of students. Evaluation of "School Culture" is done in writing and non-writing adjusted to the form of activities in the program. The success of this program lies in the active collaboration between schools, parents, the community, and the government. A note for this program is the need to instill awareness in all School Culture activities. This innovative program succeeded in triggering the appreciation of the SDIT shown by the people of Mataram.